2023
DOI: 10.1111/jdi.14029
|View full text |Cite
|
Sign up to set email alerts
|

Is a low‐carbohydrate, high‐fat diet feasible for people with type 2 diabetes and nonalcoholic fatty liver disease?

Abstract: More rigorous studies are needed to obtain robust and consistent results to provide helpful and feasible dietary recommendations for patients with type 2 diabetes and nonalcoholic fatty liver disease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, the MD diet is a dietary approach characterized by high-carbohydrate intake (50–60% of daily energy requirements at the expense of proteins and fats) and, as known, carbohydrates are the primary macronutrient that significantly affects glycemic control in subjects with diabetes. In this context, a low-carbohydrate diet (LCD) has gained attention as a potential alternative to the Mediterranean diet [ 45 ], particularly in the short term, due to its ability to facilitate greater initial weight loss [ 46 , 47 , 48 ], promote satiety and reduce hunger [ 49 ], decrease liver fat content [ 50 , 51 , 52 ], improve glycemic control and reduce the need for glucose lowering drugs in patients with T2DM [ 23 , 53 , 54 , 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the MD diet is a dietary approach characterized by high-carbohydrate intake (50–60% of daily energy requirements at the expense of proteins and fats) and, as known, carbohydrates are the primary macronutrient that significantly affects glycemic control in subjects with diabetes. In this context, a low-carbohydrate diet (LCD) has gained attention as a potential alternative to the Mediterranean diet [ 45 ], particularly in the short term, due to its ability to facilitate greater initial weight loss [ 46 , 47 , 48 ], promote satiety and reduce hunger [ 49 ], decrease liver fat content [ 50 , 51 , 52 ], improve glycemic control and reduce the need for glucose lowering drugs in patients with T2DM [ 23 , 53 , 54 , 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has shown that modifying the proportion of macronutrients in the diet can help to improve multiple metabolic diseases, such as obesity, type 2 diabetes, and non-alcoholic fatty liver disease. 14,15 For example, a low-carbohydrate dietary pattern, characterized by carbohydrate proportion ranging from 20% to 26% of the total energy intake, has been reported to lower fat accumulation in the liver. Some extremely low-carbohydrate dietary patterns with a 10% or less carbohydrate calorie proportion, termed the ketogenic diet, have been shown to improve fatty liver.…”
Section: Introductionmentioning
confidence: 99%